Rising Powers, Third-Party Threats and Reassurance:Explaining Russia's Post-Cold War Foreign PolicyToward China - Brandon K. Yoder (2019)
International Relations Theory andChina-Russia Relations after the Cold War, 3 August 2017, Singapore